2019
DOI: 10.1016/j.scitotenv.2019.06.320
|View full text |Cite
|
Sign up to set email alerts
|

Predicting uncertainty of machine learning models for modelling nitrate pollution of groundwater using quantile regression and UNEEC methods

Abstract: Although estimating the uncertainty of models used for modelling nitrate contamination of groundwater is essential in groundwater management, it has been generally ignored. This issue motivates this research to explore the predictive uncertainty of machine-learning (ML) models in this field of study using two different residuals uncertainty methods: quantile regression (QR) and uncertainty estimation based on local errors and clustering (UNEEC). Prediction-interval coverage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(65 citation statements)
references
References 91 publications
1
61
0
Order By: Relevance
“…The PICP values for the RF NO3 model of 0.91 corresponds to p (0.90), indicating correctly assessed prediction uncertainties with QRF. Other studies on prediction of groundwater nitrate concentration determined uncertainties in a similar range (Ransom et al 2017, Rahmati et al 2019. Koch et al (2019) pointed out that the uncertainty can be significantly reduced with a more comprehensive data set.…”
Section: Spatial Distribution Of Groundwater Nitrate Concentrationmentioning
confidence: 93%
See 1 more Smart Citation
“…The PICP values for the RF NO3 model of 0.91 corresponds to p (0.90), indicating correctly assessed prediction uncertainties with QRF. Other studies on prediction of groundwater nitrate concentration determined uncertainties in a similar range (Ransom et al 2017, Rahmati et al 2019. Koch et al (2019) pointed out that the uncertainty can be significantly reduced with a more comprehensive data set.…”
Section: Spatial Distribution Of Groundwater Nitrate Concentrationmentioning
confidence: 93%
“…Due to the complex processes influencing groundwater quality, estimations are accompanied by uncertainties that need to be quantified (Refsgaard et al 2007, Grizzetti et al 2015. As one of the few, Rahmati et al (2019) investigated the uncertainties in machine learning approaches for estimating groundwater nitrate concentrations and showed that it is important to consider both the performance and the uncertainty for model evaluation. Ransom et al (2017) used bootstrapping for a boosted regression tree model and Koch et al (2019) extended RF with geostatistics to assess uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the help of advance information technology, machine learning has been introduced and applied to solve a lot of real-world problems including groundwater potential mapping [11]. Recently Pal et al [12] applied the machine learning methods namely Random Forest (RF), Radial Basis Function Classifier (RBFC) and Artificial Neural Network (ANN) to assess the capacity of the groundwater potential in the Tangon watershed in eastern Indian and Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning techniques have recently gained good attention among the environmental modeling research community as they are advantageous in efficiently capturing the complex relationship between the environmental predictors and the response, such as flood [33][34][35][36][37][38][39][40][41], wildfire [42], sinkhole [43], drought [44], gully erosion [45,46], groundwater [47][48][49] and land/ground subsidence [27], and landslide in this case [3,13,[50][51][52][53][54][55][56][57]. In due course, researches have also attempted to improve the prediction accuracy and the interpretability of the models through applying various decision-trees machine learning algorithms such as chi-square automatic interaction detector; quick, unbiased and efficient statistical tree [58]; J48 decision trees [59]; ID3 decision trees [60]; random forests [61]; classification and regression trees [62]; alternating decision trees [63]; reduced error pruning trees [3]; naïve Bayes [35,53]; naïve Bayes tree [13,64]; kernel logistic regression [37]; logistic model tree [38,…”
Section: Introductionmentioning
confidence: 99%